“I'm not too old to lift”: exploring lifelong involvement in Olympic weightlifting through the serious leisure perspective - Gravelle, François; Stratas, Aida; Karlis, George (Frontiers in Sports and Active Living, 2025)
IntroductionThis study explores the lifelong involvement of older adults in Olympic weightlifting (OW) with the aim of understanding the factors that motivate them to initiate and sustain participation across their lifespan, as well as the challenges they face and the benefits they experience.MethodsSemi-structured in-depth interviews were conducted with 22 participants (18 males, 4 females), aged 50–89, who had over 30 years of training experience in OW. The interviews lasted 40–58 min and were conducted face-to-face or via video call. The data was framed through Stebbins ’serious leisure perspective with an inductive thematic analysis to identify themes.Results and discussionFive themes and four subthemes were identified that shape participants’ enduring involvement in OW: lifelong passion and commitment to OW (subthemes: perseverance and serious leisure career development), rigorous training regimens, injury experiences and recovery, self-improvement and personal growth, and social and community building (subthemes: community and camaraderie, coaching and mentorship for athlete development and legacy). These themes reveal the deep dedication, resilience, and strong sense of community that mark participants’ enduring involvement in this sport. The results suggest that OW can be utilized as a valuable sport for healthy aging, personal growth, and building supportive networks, which can inform approaches in health promotion, fitness programming, and sport development across different age groups.